Deactivation and selectivity for electrochemical ozone production at Ni- and Sb-doped SnO2 / Ti electrodes. (1st March 2020) - Sandin, Staffan; Abo Hamad, Ali; Cuartero, Maria; de Marco, Roland; Crespo, Gaston A.; Bäckström, Joakim; Cornell, Ann
Abstract: This work reports on a time-resolved study of the deactivation of electrochemical ozone production (EOP) active anodes using a novel approach to measure total ozone production. The reproducibility and change of the electrodes over time have been investigated using a number of electrochemical and physical techniques. The dissolution of antimony from the surface of the nickel- and antimony-doped tin oxide (NATO) electrode is the main process behind the deactivation of the EOP. When surface antimony is depleted, the continued deactivation seems to be connected to the dissolution of nickel. Despite tin (from the coating) and titanium (from the substrate) continuously dissolving during galvanostatic polarization of the NATO electrode, our experiments point to no connection between these processes and the EOP activity. In addition, the selectivity of the electrode is affected by electrolyte penetration, accessing fresh reaction sites that are active on the EOP. The results indicate that both antimony (III) and nickel present at the surface of the NATO are responsible for the EOP activity. Graphical abstract: Image 1 Highlights: Deactivation is mainly due to electrochemically induced antimony dis-solution. Nickel is present at the NATO surface and dissolves during polarization. The potential reading is not a su_cient indicator of the anode deactivation. All electrode components dissolve from the start of the electrolysis.